RoBlock – web app for programming learning (2016)
One of the major challenges related to teaching programming and algorithmics to amateur students is the time spent to explain a language’s syntax. Also, students who undertake computer programming may find problems that hinder their understanding of concepts and the development of their problem-solving and programming skills. This paper presents the results of an experimental approach that evaluated the interaction of a group of Colombian students with a Web solution within the context of Mobile Robotics to learn programming and algorithmics. The designed Web App is oriented towards autodidactic learning by using Visual Blocks Programming through five interactive modules that include concepts to be learned by students such as the following: variables, sensors, conditionals, cycles, and functions. The solution is designed to present virtual scenarios for Mobile Robotics. This proposal was evaluated with middle school students from the Colombian education system and was compared to the results obtained using Scratch as a reference tool.